Soil health - critical to addressing climate change and realising Africa's agricultural potential - African Union Development Agency (AUDA-NEPAD) and AICCRA (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
The guidance note unpacks the key impact of land degradation across Africa's cultivated land and impacts on food production and unpacks linkages and the impact climate change is having on increasing across Africa's agricultural landscapes. Consequently improving soil health is critical and has both adaptation and mitigation co-benefits. The guidance note summarises key practices and approaches like climate-smart agriculture for scaling up health soil practices. It also concludes with key recommendations for scaling up action on soil health across the continent.